Aesthetic and Functional Abdominoplasty: Anatomical and Clinical Classification based on a 12-year Retrospective Study. Issue 12 (20th December 2021) - Klinger, Marco; Klinger, Francesco; Giannasi, Silvia; Bandi, Valeria; Vinci, Valeriano; Catania, Barbara; Lisa, Andrea; Veronesi, Alessandra; Battistini, Andrea; Giaccone, Micol; Caviggioli, Fabio; Maione, Luca
Abstract : Background: Abdomen reshaping is a common plastic surgery procedure, and numerous surgical techniques have been described in the scientific literature. To standardize surgical approach, we propose our protocol that correlates patients' anatomy with the type of procedure performed. Methods: Between 2008 and 2020, we retrospectively analyzed 582 consecutive female patients who underwent abdomen reshaping procedures, assessing anatomical features, complication rate, patient satisfaction, and surgical result, comparing them with previous reports in the literature. Aesthetic outcomes were evaluated with VAS scale (0–10). Results: Among the 582 patients recruited in the study, we performed 74 liposuctions as a single procedure, 62 mini-abdominoplasties, 28 T-inverted abdominoplasties, and 418 full-abdominoplasties. Aesthetic outcome evaluation reported a mean value of 8.2 from patients and 7.8 from surgeons. We experienced four early postoperative bleedings requiring hemostasis revision, 18 wound dehiscences, five seromas, and 24 re-interventions for aesthetic issues. We found no differences in the complication rate while comparing our data with previous reports in the literature. Conclusions: Our protocol and surgical technique have proved to be effective, safe, and reproducible, with high patient and surgeon satisfaction, low complication rate, and fast recovery time.